The Socio-Economic Analysis of Fishermen Pertek Region in Keban Dam Lake - Dartay, Murside; Duman, Erdal; Duman, Muhsine; Atessahin, Tuncay (Ege Univ, 2009)
This study has been carried out in order to investigate the socio-economic conditions of fishermen in Keban Dam Pertek region. This region consists of Pertek fishing cooperative which are 5rd fishing region and Aydincik fishing cooperatives, which are 6rd fishing region of Keban Dam Lake. People actively engaged in fishing are between 23-52 years old and of them 80,64 % are primary school graduates, 12,90 % are secondary school graduates and 6,45 % are high school graduates. 77,41 % of these people are forced into fishing due to unemployment and carry on their father's professions. 61,29 % of them social or health security, the other 38,70 % are recorded to the SSK and BAGKUR system in addition to fishing, they also deal with agriculture and animal raising. 27 of these people (87.09 %) are married with 1-4 children. Their gross income on average is TL 40179 per person and the overall expenses are TL 30979. Their average montly income is calculated as TL 1150.
Keywords: Keban Dam Lake; Pertek; Socio-economic condition; Fisherman cooperative